PATTERN OF THE ORO-FACIAL INFECTIONS IN PATIENTS PRESENTING TO AYUB MEDICAL INSTITUTE, ABBOTTABAD. - Alamgir,; Rehman, Abdur; Ambreen Khurshid Haider,; Haris Hameed,; Wajahat Hameed,; Babar Saeed, (Journal of Ayub Medical College Abbottabad, 2022)
Background: Orofacial space infections are commonly odontogenic in origin and the anatomical locations along with mode of spread to critical areas (e.g., orbit, brain, mediastinum) can result in morbidly and mortality if not diagnosed and treated well in time. This study was aimed to analyzing the incidence and pattern of oro-facial infections. Methods: This Descriptive case series was carried out at Oral Surgery unit (Ayub Medical College) Abbottabad from January 2016 - May 2017. The sample was collected using purposive, consecutive non-probability sampling. The demographic data, infection site and clinical features were recorded. The data was analyzed by using SPSS version 21. All the descriptive variables were analyzed for percentages & frequencies. Results: Thirty-six patients were included in the study. The male (23) to female (13) ratio was (1.7:1). Right Submandibular space was most common site. In one case each, there was involvement of retropharyngeal and retromandibular space. Majority of the patients presented with swelling (88.89%). Diabetes mellitus was the most commonly found systemic disorder in the patients affecting aggressiveness of infection. Conclusion: The most common source of odontogenic facial space infections is mandibular molars resulting spread to submandibular space. Diabetes Mellitus was the most common systemic disorder affecting host immunity. The proximity of oro-facial spaces with the critical areas makes it crucial for clinicians to identify the condition promptly and provide pertinent treatment in order to avoid the fatal complications as the rate of spread of facial space infection is very rapid.